(untitled) (Comprehensive Journal of Science, 2025)
This study aims to explore the contributions of the social work profession in fulfilling the requirements of sustainable development by examining its role in addressing contemporary social challenges, developing the competencies of social workers, enhancing professional performance, and promoting community participation. The study adopted the descriptive-analytical method, which is most suitable for examining social phenomena related to professional practices and community services. Data were collected through a survey distributed to a sample of 210 social workers employed in medical and community settings within various public and private institutions. The findings revealed that the social work profession plays an active role in supporting sustainable development by providing services targeted at vulnerable groups, promoting social justice, and empowering individuals and communities at economic and social levels. The results also indicated that training programs and specialized workshops contribute to developing the skills of social workers and improving the quality of their professional performance, thereby enhancing the effectiveness of the profession in achieving sustainable development goals. Furthermore, the study highlighted the importance of using modern tools and methods in social work practice, such as digital case documentation and monitoring, to support planning and informed decision-making. The study recommends enhancing social workers’ training programs, developing institutional frameworks that support social practices, raising community awareness of the importance of social work in achieving sustainable development, and strengthening coordination among relevant stakeholders to ensure the sustainable impact of the profession on society.